1992
DOI: 10.1111/j.1365-2133.1992.tb08407.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive perforating collagenosis and Down's syndrome

Abstract: A new association is described between reacting perforating coUagenosis and Down s syndrome in a child with lupoid hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…9 Reactive perforating collagenosis (RPC), another perforating disorder, has also been reported in DS. 4,29 As opposed to the idiopathic form of EPS which is usually localized, DS EPS has a more extensive distribution of lesions and has a longer duration (Ն10 years vs. 5 years). 4,21 …”
Section: Elastosis Perforans Serpiginosa (Eps)mentioning
confidence: 99%
“…9 Reactive perforating collagenosis (RPC), another perforating disorder, has also been reported in DS. 4,29 As opposed to the idiopathic form of EPS which is usually localized, DS EPS has a more extensive distribution of lesions and has a longer duration (Ն10 years vs. 5 years). 4,21 …”
Section: Elastosis Perforans Serpiginosa (Eps)mentioning
confidence: 99%
“…Advances in medical care have led to an increased life expectancy, and, with the increasing number of individuals with DS, dermatologists are more likely to encounter the wide spectrum of skin diseases in these patients. To our knowledge, this is only the second reported association of DS and ARPC in the literature (9). Acquired reactive perforating collagenosis is probably an underdiagnosed condition, and this case illustrates the importance of recognizing rare dermatoses in individuals with DS.…”
Section: Discussionmentioning
confidence: 64%
“…In 1990 Maroon et al (9) fir.st described the milialike perforant form of cutaneous calcinosis, as an expresion of TE, in one patient with DS. On the other hand, in 1992 De Berker et al (10) reported the first DS patient with reactive petforant collagenosis, which is a primary' form of TE. More recently we have also observed three DS subjects with the milialike perforant form of cutaneous calcinosis (11,12).…”
Section: Discussionmentioning
confidence: 99%